The Lifetime Extension of Wireless Sensor Networks Using Adaptive Energy Allocation by Distance. (14th August 2013) - Liaw, Jiun-Jian; Chou, Cheng-Wei; Dai, Chen-Yi
One of the most important applications of the wireless sensor networks is the widely applied smart environment. To prolong the network lifetime, it is important to develop the protocols for reducing energy consumption because the sensor nodes are constrained by limited energy. In the cluster based on energy-efficient method, the fixed cluster head number, the energy of the node, and the transmission distance are the keys to extending the network lifetime. In this paper, we propose an improved grouping protocol, which considers the distance between the sensor node and the sink node in order to allocate total energy of a group. The proposed method is compared with previous works of simulations to show the advantages of extending the network lifetime.